Cicero in Heaven: The Roman Rhetor and Luther's Reformation. - Springer, Carl (St. Andrews studies in Reformation history., 2017)
In Cicero in Heaven: The Roman Rhetor and Luther's Reformation, Carl Springer traces the historical outlines of Cicero's rhetorical legacy, paying special attention to the momentous impact that he had on Luther, his colleagues at the University of Wittenberg, and later Lutherans. While the revival of interest in Cicero's rhetoric is more often associated with the Renaissance than with the Reformation, it would be a mistake to overlook the important role that Luther and other reformers played in securing Cicero's place in the curricula of schools in modern Europe (and America). Luther's attitude towards Cicero was complex, and the final chapter of the book discusses negative reactions to Cicero in the Reformation and the centuries that followed.